2013
DOI: 10.18287/0134-2452-2013-37-3-297-306
|View full text |Cite
|
Sign up to set email alerts
|

Features of nonparaxial propagation of gaussian and bessel beams along the axis of the crystal

Abstract: It is analytically and numerically shown that nonparaxial mode laser beams propagating along the axis of a crystal demonstrate the periodic change of intensity connected with an interference of ordinary and extraordinary beams. For Bessel beams the oscillation period inversely proportional to a square of spatial frequency of a laser beam and a difference of dielectric permittivity. For the linearly-polarized radiation there is a periodic redistribution of energy between two transversal components, and for beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The intensity distribution I(x,y,z) in the propagation of Bessel beam along the axis of the crystal is as follows [9,11,17,18]: I x, y , z   …”
Section: Theoretical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity distribution I(x,y,z) in the propagation of Bessel beam along the axis of the crystal is as follows [9,11,17,18]: I x, y , z   …”
Section: Theoretical Analysismentioning
confidence: 99%
“…It has been shown in the studies [17,18] that during the propagation along the crystal axis neuraxial Bessel beams have other properties than Gaussian beams, namely, experiencing a uniform periodic change of intensity. In this case, the Bessel beam of zero order and second-order are periodically converted from one to another [7-9, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beams of this kind are also useful for investigating optical anisotropy and birefringence. In [14][15][16][17][18][19][20][21][22] it is shown that Bessel beam propagation in birefringent crystals of various cuts is accompanied with the transformation of the beam order or kind. In [23][24][25] the influence of the position and parameters of certain elements of optical scheme (laser wavelength, illuminating beam wavefront curvature, crystal temperature) on the Bessel beam characteristics at the crystal output is analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Most often, mode and polarization conversions are needed. One tool for such transformations are anisotropic crystals [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. One method of modelling the propagation of electromagnetic waves in anisotropic media is the method of plane waves expansion [21][22][23][24][25][26].…”
mentioning
confidence: 99%